2010
DOI: 10.1093/ije/dyq057
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission risk through anal intercourse: systematic review, meta-analysis and implications for HIV prevention

Abstract: Background The human immunodeficiency virus (HIV) infectiousness of anal intercourse (AI) has not been systematically reviewed, despite its role driving HIV epidemics among men who have sex with men (MSM) and its potential contribution to heterosexual spread. We assessed the per-act and per-partner HIV transmission risk from AI exposure for heterosexuals and MSM and its implications for HIV prevention.Methods Systematic review and meta-analysis of the literature on HIV-1 infectiousness through AI was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
491
2
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 603 publications
(529 citation statements)
references
References 88 publications
18
491
2
18
Order By: Relevance
“…The latter was more common in this study when compared to patterns in other countries 1 : two RDS studies showed lower percentages 25,41 than in Salvador. However, regarding casual partners, other RDS showed similar percentages to those found in this research 27,30 , indicating high exposure of MSM in Salvador, since the probability of HIV infection can reach 40.4% per sexual partner in unprotected receptive anal sex 37 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The latter was more common in this study when compared to patterns in other countries 1 : two RDS studies showed lower percentages 25,41 than in Salvador. However, regarding casual partners, other RDS showed similar percentages to those found in this research 27,30 , indicating high exposure of MSM in Salvador, since the probability of HIV infection can reach 40.4% per sexual partner in unprotected receptive anal sex 37 .…”
Section: Discussionsupporting
confidence: 83%
“…A factor related to the sexual practices of MSM and which was associated with HIV infection and other STI is the high number of partners, which can increase their exposure to HIV infection, especially with inconsistent condom use in receptive anal sex, which can occur due to alcohol use, psychoactive substances before and during sex, or as a result of stigma and discrimination 37,38 . Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Sexual exposure is still the major transmission route for HIV, including prison inmates in Brazil, who are commonly ignored by preventive campaigns (19) . Studies have confirmed that receptive anal sexual intercourse has an increased risk of 1.4%, 18 times more in comparison with other practices (20)(21) . This practice is associated with homosexual relationships, but is also not rare in heterosexual relationships.…”
Section: Discussionmentioning
confidence: 89%
“…3 Approximately one-third of infections among newly diagnosed men in Australia are estimated to be from regular partners, [4][5][6] whereas modelling from the US estimates that 68% of infections in GBM are from 'main' partners. 7 Intimacy and familiarity with partners have been associated with increased CLAI among GBM, [8][9][10][11] and HIV prevention and research have described ongoing sexual relationships as potentially high risk for HIV transmission.…”
Section: Introductionmentioning
confidence: 99%